East Asia and the EU: The Unavoidable Partnership - Pardo, Ramon Pacheco (AEI Insights, 2021)
The bilateral relationship between East Asia and the EU is yet to develop to the same extent that US relations with each of them has. In an international system characterised by the prevalence of transnational threats to international security and the increase in number and growth in number of international institutions, East Asia–EU bilateral relations are becoming an unavoidable partnership. Indeed, relations between East Asia and the EU are becoming increasingly institutionalised as a result of shared interests, sufficient resources and expertise, the development of regional governance in each of them, and interactions at the global level. The case studies of the counter-proliferation of weapons of mass destruction and financial governance regimes show the extent to which these four elements are drawing East Asia and the EU closer to each other. Nonetheless, these two case studies concurrently exemplify the shortcomings of a relationship yet to fulfil its potential. Developing a new, well-functioning region-to-region dialogue only including East Asia and the EU would serve to create a framework for the unavoidable partnership to strengthen.